Fast‐response Electrochemical Detection of Trinitrotoluene at Sub‐ppb Levels on Nitrogenized Porous Carbon Spheres. Issue 7 (5th April 2019) - Hao, Xi‐Juan; Li, Chang‐Ming; Guo, Chunxian
Abstract: We present sub‐ppt level detection of explosive trinitrotoluene by constructing a fast‐response electrochemical sensor using nitrogenized porous carbon spheres (NPCS). NPCS with nitrogen doping and amino functionalization accelerates charge transfer and trinitrotoluene accumulation. A high sensitivity of 60.2 μA cm −2  ppb −1 and a detection limit of 0.15 ppb are achieved on NPCS, among the best of recently reported trinitrotoluene electrochemical sensors. Moreover, response time of NPCS is greatly reduced by two times comparing with nitrogen‐free sample. NPCS also offers high selectivity, repeatability and stability, rendering new opportunities to fast detect trinitrotoluene for home security and environment protection. Abstract :